Insulin degludec is associated with less frequent and milder hypoglycemia in insulin-deficient patients with type 1 diabetes compared with insulin glargine or detemir - Iwasaki, Shingo (Diabetol Int, 2017)
INTRODUCTION: The aim of this study was to determine the efficacy of insulin degludec (IDeg) relative to insulin glargine (IGlar) or insulin detemir (IDet) in glycemic control, as evaluated by continuous glucose monitoring (CGM) in insulin-deficient patients with type 1 diabetes. METHODS: We studied 28 outpatients treated with IGlar or IDet (IGlar/IDet). Basal insulin was switched to IDeg when glycemic control was considered unstable, as judged by the dawn phenomenon or nocturnal hypoglycemia. Whole-day CGM data were also divided into daytime and nighttime data. RESULTS: The dawn phenomenon or nocturnal hypoglycemia under IGlar/IDet treatment was observed in all patients. Among 26 patients who completed the study, there were no significant differences in parameters representing glycemic variability, hyperglycemia, mean glycemic control, and HbA1c or insulin therapy-related quality of life at the night score. Measures of hypoglycemia [whole-day %Low and area under the curve (AUC) below 70] were significantly lower under IDeg treatment than under IGlar/IDet treatment (%Low, 9.6 ± 11.5 vs. 14.7 ± 14.9%, p = 0.045; AUC below 70, 85.5 ± 126.0 vs. 145.0 ± 178.6 mg/dl h, p = 0.030). Dividing patients into two groups according to percentage or degree of hypoglycemia under IGlar/IDet treatment, the whole-day, daytime and nighttime %Low in the high-percentage groups and AUC below 70 in the high-degree groups were significantly ameliorated, respectively (p < 0.05). CONCLUSION: Patients with unstable glycemic control under IGlar/IDet treatment did not improve glycemic control upon switching to IDeg, but the frequency and the degree of hypoglycemia was reduced in insulin-deficient outpatients with type 1 diabetes, especially in those suffering from severe hypoglycemia. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13340-017-0303-5) contains supplementary material, which is available to authorized users.